PENGEMBANGAN MODUL PEMBELAJARAN ILMU PENGETAHUAN ALAM BERBASIS STEM (SCIENCE, TECHNOLOGY, ENGINEERING, AND MATHEMATICS) UNTUK MENINGKATKAN BERPIKIR KRITIS SISWA SD/MI - Ilma Siti Anisa; Retno Triwoelandari; Yono Yono (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2022)
The purpose of this study is to determine the effectiveness of developing natural science learning modules based on STEM (Science, Technology, Engineering, and Mathematics) to improve critical thinking and suitable for use for learning natural sciences in grade IV SD/MI. This research method uses research and development or is called Research and Development (RD) which refers to the ASSURE development model. The subject of this research is class IV SDIT Khoiru Ummah. This learning module goes through the stages of expert validation. The result show based on the results of the validation of the learning module, it was declared feasible to use, seen from the results of design validation, which obtained 76.31%, language validation 87.5% and material validation 71.5%. In addition, the increase in students' critical thinking was declared effective. Based on the results of the large group which was divided into 2, namely the experimental class got greater results than the control class. From the results presented, the STEM-based natural science learning module (Science, Technology, Engineering, and Mathematics) is suitable for use by fourth graders and is effective in improving critical thinking of fourth grade elementary/MI students.